Surgical Outcomes of Correction of Upper Eyelid Retraction in Thyroid Eye Disease - Veda Charissa; Hernawita Suharko (Majalah Oftalmologi Indonesia, 2021)
Purpose: to evaluate the outcome of anterior blepharotomy in correcting eyelid retraction in patients with Thyroid Eye Disease (TED). Methods: Literature search was conducted from MEDLINE database through PubMed, Google scholar and ClinicalKey. Outcomes included margin-reflex distance, palpebral fissure height, and upper eyelid margin-superior limbus distance. Results: Sixteen articles were reviewed with a mean follow-up time in the studies varied, ranging from 6 to 61 months. The preoperative and postoperative mean MRDs varied. Although there were different success criteria, success rate for full thickness blepharotomy ranged from 59-93%, comparable with levator recession. The complication rates in 14 studies were less than 20%. Conclusion: Full thickness anterior blepharotomy and Müller muscle and levator recession, are safe and effective in correcting upper eyelid retraction in patients with TED. The anterior blepharotomy is a relatively quick and simple procedure.